DISPERSIÓN SECUNDARIA DE SEMILLAS POR ESCARABAJOS COPRÓFAGOS (SCARABAEIDAE) A PARTIR DE HECES DE CHURUCOS (LAGOTHRIX LAGOTHRICHA) EN EL PARQUE NACIONAL TINIGUA, COLOMBIA - Laverde Angarita, Lilia Judith; Departamento de Ciencias Biológicas, Universidad de Los Andes, Bogotá (2013)
The activity of dung beetles (Scarabaeidae) associated with woolly monkey (Lagothrix lagothricha) dung, assecondary seed dispersal agents, was studied in Tinigua National Park, Meta, Colombia. From 62 dung sampleswe estimated a mean range of 30-33 small seeds, 3-5 medium seeds and 0-1 large seeds by fragment. The meanduration from the deposition of each dung fragment to dung beetle arrival was 3,2 hours. The means of horizontal17Universítas Scientiarum Vol. 7, N° 1: 17-29and vertical seed postdispersal distance was variable depending on dung beetle type: For the ball roller: 60,6 cm(±1 ,7 cm) and 0,8 cm (±o,2 cm) respectively; for fragment roller: 10,2 cm(± 0,2 cm) and 5,5 cm (±o,6cm) and forthe burrower's vertical remotion was O, 1 cm without horizontal remotion. The longest horizontal removal distan cewas presented by a ball roller.beetle Cantlwn luteicol/is (272 cm). Of 74 individual dung beetles observed, 37were catalogued as piece rollers, 27 as ball rollers and 10 as strict burrowers. The mean arrival times to dungpieces was smaller for rollers than for burrowers. We observed selection of dung material, as well as cooperationand competition between species and within species by dung beetles. The remotion distance of seeds resultedinversely proportional with its size. These observations suggest that not only the initial dispersa! by woolly monkeysand the posterior distribution of dung in the moment of deposition play an important role linked to the success orfailure of the seeds, but the relocation by the dung beetles also contributed to the general dispersa! process.